LA SEGURIDAD EN LOS CAMPOS DE FÚTBOL: UN ESTUDIO A PARTIR DEL ESTADIO CASA BLANCA (QUITO, ECUADOR) 1 - Lic. Pedro David ESPINOZA ORDÓÑEZ,Dr. Daniel BARREDO IBÁÑEZ,Mtra. Montserrat FERNÁNDEZ VELA (Fonseca, Journal of Communication, 2023)
By violence, we understand the actions that an individual or a group of individuals committed with the purpose of causing harm to others or their property. In this conceptual scope of violence, we highlight the role of the attacks in the environment of football, where certain groups of fans —rather than acting as passive observers of the game— profane the statism of the viewer to manifest violent behaviors; we refer in particular to the hooligans or the ultras.